157k views
22 votes
Match each sum or difference with the correct simplified expression.

(x - 5) - (x - 1)

2x - 4

(x - 5) + (x + 1)

2x - 6

(x - 5) - (x + 1)

4.

(x - 5) + (x - 1)

-6

2 Answers

7 votes

Answer:

Explanation:

I got it right on edge 2022!

Match each sum or difference with the correct simplified expression. (x - 5) - (x-example-1
User Adrin
by
4.7k points
2 votes

Answer:


(x-5)-(x-1)=-4


=2x-4


(x-5)+(x+1)=-6


(x-5)+(x-1)=2x-6

Explanation:

In each of the expressions we first need to open the brackets and change the sign according to the sign preceding the bracket. After that we perform simple arithmetic to find the result.


(x-5)-(x-1)=x-5-x+1


=-4


(x-5)+(x+1)=x-5+x+1


=2x-4


(x-5)-(x+1)=x-5-x-1


=-6


(x-5)+(x-1)=x-5+x-1


=2x-6

The answers are


(x-5)-(x-1)=-4


(x-5)+(x+1)=2x-4


(x-5)+(x+1)=-6


(x-5)+(x-1)=2x-6

User Shahrukh Mohammad
by
5.1k points